The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3109/08880018.2015.1040932
|View full text |Cite
|
Sign up to set email alerts
|

Thalassemia Intermedia Caused by 16p13.3 Sectional Duplication in a β-Thalassemia Heterozygous Child

Abstract: Thalassemia intermedia is an inherited hemoglobin disorder characterized by a significant genetic and clinical heterogeneity. A wide spectrum of different genotypes-homozygous, heterozygous, and compound heterozygous-have been found to be responsible for it. The authors describe a Chinese child of β-thalassemia heterozygote with the mutation IVS2-654 (C→T) (HBB:c.316-197C→T) presenting with severe thalassemia intermedia. Multiplex ligation-dependent probe amplification (MLPA) and array comparative genomic hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Probes are not placed in repetitive regions of the genome, and the assay is not able to detect balanced rearrangements. CGH array has been used with some success to detect SVs causing hemoglobinopathies …”
Section: Introductionmentioning
confidence: 99%
“…Probes are not placed in repetitive regions of the genome, and the assay is not able to detect balanced rearrangements. CGH array has been used with some success to detect SVs causing hemoglobinopathies …”
Section: Introductionmentioning
confidence: 99%
“…To date, seven other segmental HBA cluster duplications have been documented, including the anti‐3·7 and ‐4·2 triplicated HBA genes (Sollaino et al , ; Harteveld & Higgs, ; Jiang et al , ; Liu et al , ). These three additional cases take the total to 10 (Fig ).…”
mentioning
confidence: 99%
“…Copy number variations in the form of multiplications of α genes can cause a severe phenotype in β‐thalassemia carriers due to accentuation of α/β globin chain imbalance. Previous studies, including our two cases, showed that six active α genes could result in severe β‐thalassemia intermedia or β‐thalassemia major in β‐thalassemia heterozygotes. These might be the reason, at least, for a part of the many unclear cases of severe phenotype in β‐thalassemia carriers.…”
Section: Discussionmentioning
confidence: 57%